Business plan and financial feasibility study of “Prata Bubuhan” breakfast UMKM stall in Indragiri Hilir Regency - Uya Asy Syuura Anandri (Priviet Social Sciences Journal, 2025)
Prata Bubuhan is a business engaged in the culinary field with a contemporary and modern concept that markets household needs products, such as breakfast and various types of drinks. This study aims to evaluate the economic viability of the venture and provide managerial recommendations for startup implementation. Primary financial analysis is based on projected cash flows and investment appraisal techniques, including Net Present Value (NPV), Internal Rate of Return (IRR), Profitability Index (PI), Break-Even Point (BEP), and payback period, with a discount rate assumed at 10%. The results indicate that the project requires an initial capital of IDR 150,000,000 and yields a positive NPV of IDR 121,560,300, an IRR of approximately 33.51%, a PI of 1.81, and an estimated payback period of about 2.56 years. These findings suggest that the Prata Bubuhan venture is financially viable under the stated assumptions. This study contributes to the literature on micro, small, and medium enterprises (MSMEs, locally known as UMKM) by providing an empirical case of a food-based UMKM in Indonesia, discussing the sensitivity of outcomes to key assumptions (sales growth and cost variations), and offering practical recommendations on pricing, cost control, and operational planning to enhance project sustainability and investor appeal.